Everyday politics in the Libyan Arab Jamahiriya - Capasso, Matteo (Modern intellectual and political history of the Middle East., 2023)
"The book provides a vivid account of the intricate dynamics of power that characterized the Libyan Arab al-Jamahiriyah through the eyes of its own people. The research is based on the collection of sixty-six oral histories with Libyan individuals, who had all left the country in the aftermath of 2011, and took place in the United Kingdom and Italy through 2015-17"--